On some systems of nonlinear integral Hammerstein-type equations on the semiaxis - Khachatryan, Kh. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We prove the existence for a one-parameter family of solutions of a system of nonlinear integral Hammerstein-type equations on the positive semiaxis and study the asymptotic behavior of the obtained solutions at infinity.